PENGARUH PERMAINAN PUZZLE PASIR TERHADAP KECERDASAN VISUAL SPASIAL PADA ANAK USIA 5-6 TAHUN DI TK EDUCATION 21 KULIM KOTA PEKANBARU - Senawati, Rika Muji; Indarto, Wusono; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aims to know the influence of the game a puzzle sand to intteligence visual spasial of 5-6 years old children in Education 21 Kindergarten Kulim of Pekanbaru City. Population of this reseacrh in Education 21 Kindergarten Kulim of Pekanbaru City. Sample of researchare 19 childs. Method of research was experiment which this research tries to look for this research aim to know the influence of the game a puzzle sand to intteligence visual spasial of 5-6 yeard old children in Education 21 Kindergarten Kulim of Pekanbaru City. Instrumental of this research used observation sheet. Data anlisa tech used utilizes scale test-driving and statistical methods analysis with SPSS For's program ver's Windows 18. The result of this research that acquired available the influence of the game a puzzle sand to intteligence visual spasial of 5-6 yeard old children in Education 21 Kindergarten Kulim of Pekanbaru City. 18 in tara signifikansi 5 % (2-tailed) of 2,101. Thus known t a (27,496)>t tabel (2,101) or signifikansi (0,000)<5% (0,005). So, its mean that Ho refused and Ha accepted that means there are very significant different between before and after doing the experiment with puzzle sand.Key Words:Visual Spasial intelligence, Puzzle sand